Teaching writing to Students of English as a foreign language: The Challenges Faced by Teachers - Zanyar Ghafar (RADINKA JAYA UTAMA PUBLISHER, 2023)
Teaching writing to students who need a more strong command of the English language presents a unique set of challenges for their instructors. People who are not native English speakers may find it challenging to enhance their writing talents due to language barriers, cultural differences, and a lack of knowledge of writing standards. This may make it difficult for students to improve their writing abilities. It is within one's power to succeed despite these challenges. Despite this, it is possible to do this successfully with enough preparation, well-targeted teaching strategies, and a friendly and welcoming atmosphere for learning. This article will analyze the challenges teachers face when teaching writing to students whose first language is not English and will present actionable suggestions to enhance these students' educational experiences. The article will also discuss the problems teachers face when teaching writing to students whose first language is not English